Crouching Tiger, Ascending Dragon: The Trends and Dynamics of Malaysia-China Relations - Lai, Yew Meng; Maureen De Silva; Wang Yunqi (Penerbit Universiti Sains Malaysia, 2023)
This article examines the trends and dynamics of Malaysia-China relations, with emphasis on the post-Cold War era and beyond. More specifically, it explicates the interplay of external and domestic dynamics that have defined Malaysia’s China policy amid shifting regional strategic and domestic political milieu. This article contends that Malaysia’s “hedging” policy vis-à-vis China has been primarily shaped by the country’s ruling-elite’s perceptions of its external conditions in the context of East Asia’s evolving power dynamics, tempered by their domestic political expediency. It further argues that despite the periodical recalibrations having given the impression of policy-shifts, they have not fundamentally altered Malaysia’s China policy-approach. Instead, continuity rather than change has been the hallmark, since the “structural conditionalities” driving and constraining Malaysia’s relations with China continue to be informed by Malaysian rulingelite’s domestic political considerations, as they strive to optimise as much the country’s external interests, as to consolidate their domestic legitimacy. The findings inform Putrajaya’s persistence on “light-hedging” as the optimal policyoption, when dealing with Beijing, to advance Malaysia’s national survival and interests as a “smaller-state”, amid the evolving regional geopolitics, shaped by power asymmetry, rivalry and uncertainty.